A simple water treatment procedure using a moringa activated two-tier filtration and Nano-silver impregnated ceramic pot system - M. Akpomie, Timothy; P. I Ogah, S.; Ngunan Patience, Wombo; Pheobe Sorphy, Samuel; Lawrencia, Labaran; E. Jonathan, Okewu; Amos Edekioyaihegbo, Ohiobo (International Journal of Advanced Chemistry, 2022)
This study was aimed at investigating the effectiveness of a customized ceramic pot treated with moringa oleifera and coated with silver sulphate solution for domestic water treatment. The customized pots were made by combining clay with sawdust at different ratios of 10:90, 20:80, 30:70, 40:60 and 50:50 respectively then coated with colloidal silver. The results obtained from all filtration pots indicated a 100% removal of coliform bacteria and Escherichia coli and were thus suitable for deployment in drinking water treatment. All ratios of the filtration pots were found to be effective, however, the 60:40 was found to be more practicable because of its higher filtration rate. Additionally, it was noted that the various filtration pots were very effective in lowering the higher values of the physicochemical parameters of pH, TS, TDS, TSS and turbidity as compared to the values of the world health organization (WHO) standard. This filtration method was however, not very effective in the reduction of the elemental concentration of the respective raw water samples. Overall, the results obtained encouraged the use of the two-tier filtration system especially in rural and developing areas where sophisticated dosing equipment or appropriate dose of the moringa oleifera is not required as different dosages were all effective and did not pose any undesirable effect on the physicochemical and elemental composition of the treated water samples.Â Â